Heterogeneous social motives and interactions: The three predictable paths of capability development - Bridoux, Flore; Coeurderoy, Régis; Durand, Rodolphe (Strategic Management Journal, 2017)
Research summary : L imited attention has been paid to the crucial role of individuals' motivation and social interactions in capability development. Building on literature in social psychology and behavioral economics that links heterogeneity in individual social motives to social interactions, we explain how the variation, selection, and retention processes underlying a group's deliberate capability development are affected by the composition of the group in terms of individuals' social motives in interplay with the organizational‐level motivational levers designed by managers. Our multilevel theoretical model suggests that individual‐level heterogeneity leads to the development of capabilities along different paths. For practice, this implies that, according to the composition of the group in terms of social motives, capabilities are more or less technically and evolutionary adequate and a source of business process performance. Managerial summary :We propose that when a group of employees engages in developing one of the firm's capabilities, capability development will follow a different path according to what motivates most of the employees composing the group. We identify and discuss three paths. Two of these paths (convergence and congruence) can help improve business process performance in a stable environment, the third one (open‐ended) in a dynamic environment. Our work invites managers to not only think in terms of more or less capability development, but also in terms of capability development path(s): the path(s) in which groups in the firm are currently engaged and the one(s) that are desirable given the firm's objectives and the nature of the environment(s) the firm faces in deploying its business processes. © 2016 The Authors. Strategic Management Journal published by John Wiley & Sons, Ltd.